A study of factors affecting the symbiosis between two varieties of Lupinus angustifolius L. and two isolates of Rhizobium lupini (Schroeter) Ekhardt, Baldwin & Fred - Bezuidenhout, S. J. P. K.(Stephanus Johannes Paulus Kruger) (Stellenbosch : Stellenbosch University, 2012)
Thesis (DSc) -- University of Stellenbosch, 1964.